Translating research evidence into practice: a report from the 2nd International Conference on Maternal and Newborn Health from KLE University - Belagavi, India - Robert L. Goldenberg; Elizabeth M. McClure; José M. Belizán (BMC, 2018)
Abstract The Jawaharlal Nehru Medical College (JNMC) Women's and Children's Health Research Unit (WCHRU) of the Karnataka Lingayat Education (KLE) Academy of Higher Education and Research Deemed-to-be-University and its collaborators convened the '2nd International Conference on Maternal and Newborn Health -Translating Research Evidence to Practice' to address the common theme of improving maternal and newborn health in low- and middle- income countries (LMIC). This supplement, including 16 manuscripts, reflects much of the research presented at the conference, including analyses of the state of knowledge, as well as completed, ongoing and planned research in these areas conducted by the WCHRU in India together with many collaborators across high-income and LMIC. The first paper reviews maternal, fetal and neonatal mortality in low-income countries, considers their causes, as well as evidence for potential interventions to reduce mortality. A second paper addresses near miss maternal mortality. Several manuscripts address the research conducted by WCHRU and their colleagues in a multi-center research network. One study examines rates of miscarriage and medically terminated pregnancy in India and the risk factors for these occurrences. Another paper addresses stillbirth and its risk factors, both in India as well as in other LMIC. Haemorrhage and preeclampsia/eclampsia, important causes of maternal mortality, stillbirth and neonatal morbidity in LMIC, are addressed in a series of papers summarizing trials of interventions to reduce improve outcomes associated with these conditions. Poor maternal and infant nutritional status, which contribute to adverse outcomes, are addressed through papers which describe a number of important studies that the WCHRU and their colleagues have conducted to attempt to improve nutritional status. Another paper describes a study to investigate causes of stillbirth and deaths among preterm births, which will utilize new techniques to investigate the infectious causes of these deaths. Finally, the supplement addresses the process for dissemination of research results to inform public policy. Together these manuscripts represent a body of research to inform interventions to reduce maternal, fetal and newborn mortality and illustrates what a dedicated research group together with institutional support can accomplish.